Regional impacts of the New Hungary Rural Development Program - Keszthelyi, Krisztián (Studia Mundi – Economica, 2019)
The preparation of my thesis was basically motivated to examine the operation of the Hungarian subsidy system in order to give some modifying proposals to develop the efficiency of the system. The territorial effects have played main role in my studies, which’s results are presented in this study. On the whole the result is identified that the subsidy system needs more effective operation and there are potentials to increase the efficiency.